Free Fatty Acids and Their Inflammatory Derivatives Affect BDNF in Stroke Patients - Dariusz Kotlega; Agnieszka Zembron-Lacny; Barbara Morawin; Monika Golab-Janowska; Przemyslaw Nowacki; Malgorzata Szczuko (Hindawi Limited, 2020)
Objective. The neurotrophin brain-derived neurotrophic factor (BDNF) affects poststroke functional outcome, neurogenesis, neuroprotection, and neuroplasticity. Its level is related to the diet and nutritional status, and more specifically, it is free fatty acids (FFAs) and eicosanoids that can have an impact on the BDNF level. The aim of this study was to analyze the potential impact of FFAs and eicosanoids on the BDNF level in stroke patients. Material and Methods. Seventy-three ischemic stroke patients were prospectively enrolled in the study. Laboratory tests were performed in all subjects, including the levels of FFAs, eicosanoids, and BDNF. FFAs and inflammatory metabolites were determined by gas chromatography and liquid chromatography, while BDNF was evaluated by the immune-enzymatic method (ELISA). Results. The plasma level of BDNF negatively correlated with C22:1n9 13 erucic acid, C18:3n3 linolenic acid (ALA), and lipoxin A4 15-epi-LxA4. A direct association was observed in relation to BDNF and C16:1 palmitoleic acid and C20:3n6 eicosatrienoic acid (dihomo-gamma-linolenic acid (DGLA)). Conclusions. Saturated fatty acids and omega-3 and omega-9 erucic acids can affect signaling in the BDNF synthesis resulting in the decrease in BDNF. There is a beneficial effect of DGLA on the BDNF level, while the effect of ALA on BDNF can be inhibitory. Specialized proresolving lipid mediators can play a role in the BDNF metabolism. BDNF can interact with inflammation as the risk factor in the cardiovascular disorders, including stroke.